Cutting parameter and tool path style effects on cutting force and tool deflection in machining of convex and concave inclined surfaces - Gok, Arif; Gologlu, Cevdet; Demirci, Halil Ibrahim (Springer Science and Business Media LLC, 2013)
Convex and concave inclined surfaces are frequently encountered in the machining of components in industries such as aerospace, aircraft, automotive, biomedical, and precision machinery manufacturing and mold industries. Tool path styles, generated by different cutting strategies, result in various cutting forces and tool deflection values that might lead to poor surface integrities. In cost-effective manufacturing, it is helpful to make known their effects on machinability. Thus, the first aim of this study is to investigate optimum cutting parameter values in ball end milling of EN X40CrMoV5-1 tool steel with three coated cutters. The parameters taken into consideration are cutting speed, feed rate, step over, and tool path style. The second aim of the study is to determine the effects of tool path styles in ball end milling of inclined surfaces. As a result, the most effective parameter within the selected cutting parameters and cutting styles for both inclined surfaces and different coatings was step over. In terms of tool coatings, the most rapidly deteriorating coating was TiC coating for cutting forces in both inclined surfaces and for tool deflection in convex inclined surface. In addition, the response surface methodology is employed to predict surface roughness values, depending on the cutting forces obtained. The model generated gives highly accurate results.